Increase of Dose Associated With Decrease in Protection Against Controlled Human Malaria Infection by PfSPZ Vaccine in Tanzanian Adults. (29th November 2019) - Jongo, Said A; Church, L W Preston; Mtoro, Ali T; Schindler, Tobias; Chakravarty, Sumana; Ruben, Adam J; Swanson, Phillip A; Kassim, Kamaka R; Mpina, Maximillian; Tumbo, Anneth-Mwasi; Milando, Florence A; Qassim, Munira; et al.
Abstract: Background: A vaccine would be an ideal tool for reducing malaria's impact. PfSPZ Vaccine (radiation attenuated, aseptic, purified, cryopreserved Plasmodium falciparum [Pf] sporozoites [SPZ]) has been well tolerated and safe in >1526 malaria-naive and experienced 6-month to 65-year-olds in the United States, Europe, and Africa. When vaccine efficacy (VE) of 5 doses of 2.7 × 10 5 PfSPZ of PfSPZ Vaccine was assessed in adults against controlled human malaria infection (CHMI) in the United States and Tanzania and intense field transmission of heterogeneous Pf in Mali, Tanzanians had the lowest VE (20%). Methods: To increase VE in Tanzania, we increased PfSPZ/dose (9 × 10 5 or 1.8 × 10 6 ) and decreased numbers of doses to 3 at 8-week intervals in a double blind, placebo-controlled trial. Results: All 22 CHMIs in controls resulted in parasitemia by quantitative polymerase chain reaction. For the 9 × 10 5 PfSPZ group, VE was 100% (5/5) at 3 or 11 weeks ( P < .000l, Barnard test, 2-tailed). For 1.8 × 10 6 PfSPZ, VE was 33% (2/6) at 7.5 weeks ( P = .028). VE of dosage groups (100% vs 33%) was significantly different ( P = .022). Volunteers underwent repeat CHMI at 37–40 weeks after last dose. 6/6 and 5/6 volunteers developed parasitemia, but time to first parasitemia was significantly longer than controls in the 9 × 10 5 PfSPZ group (10.89 vs 7.80 days) ( P = .039), indicating a significant reduction in parasites in the liver. Antibody and T-cell responses were higher in the 1.8 × 10 6 PfSPZ group. Conclusions: In Tanzania, increasing the dose from 2.7 × 10 5 to 9 × 10 5 PfSPZ increased VE from 20% to 100%, but increasing to 1.8 × 10 6 PfSPZ significantly reduced VE. Clinical Trials Registration: NCT02613520. Abstract : In Tanzania, increasing the total dosage of PfSPZ Vaccine from 1.35 × 10 6 to 2.7 × 10 6 PfSPZ, increased vaccine efficacy from 20% to 100%, but increasing the dosage further to 5.4 × 10 6 PfSPZ was associated with reduction of vaccine efficacy to 33%.